a. By the chain rule,
h'(x) = f'(g(x)) * g'(x)
h'(1) = f'(g(1)) * g'(1) = f'(1) * 1 = 3
b. I suspect there's a typo here somewhere, but if you really mean j(x) = f(x), and you're only supposed to find j(1), then
j(1) = f(1) = 2
Possibly you're supposed to instead find j'(1), in which case
j'(1) = f'(1) = 3
Or maybe j is defined like
j(x) = 1/f(x)
in which case the chain rule gives
j'(x) = -f'(x)/f(x)^2
j'(1) = -f'(1)/f(1)^2 = -3/2^2 = -3/4
c. By the chain rule,
k'(x) = g'(x)/g(x)
k'(1) = g'(1)/g(1) = 5/1 = 5